Metastatic and recurrent adrenocortical cancer is not defined by its genomic landscape - Tito Fojo; Lyn Huff; Thomas Litman; Kate Im; Maureen Edgerly; Jaydira del Rivero; Stefania Pittaluga; Maria Merino; Susan E. Bates; Michael Dean (BMC, 2020)
Abstract Background Adrenocortical carcinoma (ACC) is a rare, often-aggressive neoplasm of the adrenal cortex, with a 14-17 month median overall survival. We asked whether tumors from patients with advanced or metastatic ACC would offer clues as to putative genes that might have critical roles in disease progression or in more aggressive disease biology. Methods We conducted comprehensive genomic and expression analyses of ACCs from 43 patients, 30 female, and 42 from metastatic sites, including deep sequencing, copy number analysis, mRNA expression and microRNA arrays. Results Copy number gains and losses were similar to that previously reported for ACC. We identified a median mutation rate of 3.38 per megabase (Mb). The mutational signature was characterized by a predominance of C > T, C > A and T > C transitions. Only cancer genes TP53 (26%) and beta-catenin (CTNNB1, 14%) were mutated in more than 10% of samples. The TCGA-identified putative cancer genes MEN1 and PRKAR1A were found in low frequency-4.7 and 2.3%, respectively. The majority of the mutations were in genes not implicated in the etiology or maintenance of cancer. Specifically, amongst the 38 genes that were mutated in more than 9% of samples, only four were represented in Tier 1 of the 576 COSMIC Cancer Gene Census (CCGC). Thus, 82% of genes found to have mutations likely have no role in the etiology or biology of ACC; while the role of the other 18%, if any, remains to be proven. Finally, the transcript length for the 38 most frequently mutated genes in ACC is statistically longer than the average of all coding genes, raising the question of whether transcript length in part determined mutation probability. Conclusions We conclude that the mutational and expression profiles of advanced and metastatic tumors are very similar to those from newly diagnosed patients-with very little in the way of genomic aberration to explain differences in biology. With relatively low mutation rates, few major oncogenic drivers, and loss of function mutations in several epigenetic regulators, an epigenetic basis for ACC may be postulated and serve as the basis for future studies.